2015
DOI: 10.1097/aog.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Optimal, Suboptimal, and Questionably Appropriate Receipt of Antenatal Corticosteroid Prophylaxis

Abstract: Temporal increases in optimal exposure to antenatal corticosteroids have been matched by increases in suboptimal and questionably appropriate receipt of antenatal corticosteroids, highlighting the need for accurate preterm delivery prognostic models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 24 publications
4
75
3
3
Order By: Relevance
“…Among all live births in Nova Scotia, Canada, optimal ACS receipt increased from 10% in 1988 to 23% in 2012 [10]. Among Dutch women with singleton, twin or triplet pregnancies, and preterm labor who completed a first course of ACS, 32% delivered with optimal timing of ACS.…”
Section: Commentmentioning
confidence: 99%
“…Among all live births in Nova Scotia, Canada, optimal ACS receipt increased from 10% in 1988 to 23% in 2012 [10]. Among Dutch women with singleton, twin or triplet pregnancies, and preterm labor who completed a first course of ACS, 32% delivered with optimal timing of ACS.…”
Section: Commentmentioning
confidence: 99%
“…This makes it difficult to maximise ‘optimal’ use of corticosteroids (i.e., administration to women who go on to deliver within the next 7 days and not administering them to women who do not deliver within the next 7 days). A recent study from Nova Scotia, Canada, showed that between 1988 and 2012, the proportion of women with suboptimal antenatal corticosteroid treatment (i.e., more than 7 days prior to delivery) increased approximately 5 times (from 7% to 34%) whereas optimal treatment doubled (from 10% to 23%) [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In all live births in Nova Scotia from 1998-2012, the rates of suboptimal treatment were 34% (odds ratio 6.7, 95% CI 3.9-11.6) and questionably appropriate treatment of 1.7% (odds ratio 7.5, 95% CI 4.9-11.3). 37 In fact, in 2012, more than half the newborns whose mothers received ANCS were born at 35 weeks gestation, and thus were unnecessarily exposed. 37 Another study demonstrated that of 692 women receiving ANCS at a single institution, 35.7% delivered at or >34 weeks gestation, and 17.9% remained pregnant beyond a week after ANCS and were still <34 weeks.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…37 In fact, in 2012, more than half the newborns whose mothers received ANCS were born at 35 weeks gestation, and thus were unnecessarily exposed. 37 Another study demonstrated that of 692 women receiving ANCS at a single institution, 35.7% delivered at or >34 weeks gestation, and 17.9% remained pregnant beyond a week after ANCS and were still <34 weeks. 38 A rescue dose of steroids is often used in these situations; however, multiple courses of ANCS are not recommended due to poor fetal head growth and increased risk of neurodevelopmental impairment by 5 years.…”
Section: A N U S C R I P Tmentioning
confidence: 99%